Nutritional aspects of producing fruits organically - Nagy, P. T.; Nyéki, J.; Szabó, Z. (International Journal of Horticultural Science, 2010)
Recent interest to avoid use of agrochemicals in fruit growing to safeguard environmental and human health has stimulated interest in organic fruit production (OFP) all over the world. Organic production requires a holistic approach to agricultural ecosystem management. Because of the perennial nature of orchards, this is not a great departure from conventional orchard management, except that corrective techniques are limited primarily to naturally derived materials. Organic mineral nutrition management hinges on two principles: 1) practices that lead to the build up and maintenance of soil that is biologically active and high in organic matter; 2) supplementing the mineral nutrients provided by the soil with fertilizers from approved sources. Organic orchards should be sited on land with superior soils and preplant soil preparation to increase organic matter and correct any sub-optimal soil characteristics. For successful organic fruit growing the following statement should be considered:Weed management is critical to reduce competition for nutrients and water. Soil and leaf analysis provide the basis for correcting mineral nutrient deficiencies or imbalances in organic production. It may be necessary to use a number of strategies to supply mineral nutrients over the life of the orchard. The slower, natural methods applied require a management approach that is simultaneously patient and dynamic.